Utilization of Legal Education Digitalization for Village Heads in Empowering Village Owned Enterprises - Wiryadi, Uyan (JTP - Jurnal Teknologi Pendidikan, 2023)
Most of Indonesia's population lives in rural areas, for this reason it is necessary to prioritize development to improve public services and the village economy in order to form individuals and communities to become self-reliant. One of the government's efforts is to implement a village digitization program. Digitalization through the use of this technology really needs to be implemented on a micro-scale development located in rural areas such as village-owned enterprises. The research method used is descriptive research. The results of the study show that digitalization of legal education has a very crucial role for the village head in empowering Village-Owned Enterprises (BUMDes), one of which will increase sufficient capacity and knowledge so that they can properly run and empower BUMDes. In addition to technical skills such as accounting and managerial skills, character-deepening training is also needed in order to produce honest and trustworthy BUMDes staff managers. BUMDes specifically cannot be equated with legal entities such as limited liability companies or cooperatives. in conclusion, the status of BUMDes after the issuance of Law Number 11 of 2020 concerning Job Creation, namely as a New Entity Legal Entity whose position is equivalent to BUMN at the national level and BUMD at the regional level.